INDEPENDENT FOOD PRODUCTION AS IMMEDIATE GASTRONOMICAL AUTHENTICITY OF THE REGION OF IMPORTANCE FOR THE DEVELOPMENT OF TOURISM IN VOVODINA - Kalenjuk Pivarski, Bojana M; Grubor, Biljana; Djercan, Bojan; Ivanovic, Velibor (The Business of Tourism, 2022)
Gastronomy and food production and preparation in certain areas reflect the cultural and traditional characteristics of people who live there. Vojvodina is characterized by a variety of cuisines of the people who lived and still live in this area. This study will attempt to depict the differences in the production of agricultural and food products in Vojvodina’s households, as well as the basics for the preservation of authenticity and traditional values of gastronomy. The aim of this work is to examine the representation of agricultural and food production in counties of Vojvodina and which county has the most potential to attract food-oriented tourists. The research is conducted through a survey questionnaire among the residents of Vojvodina. The research is conducted from October 2020 to May 2021. 619 respondents took part in the research. The data collected were processed by applying descriptive statistics, which are then presented tabularly and graphically. This research concludes that traditional values in Vojvodina are preserved through production of agricultural and food products inside this area. The south part of Bačka has the most potential for the development of tourism, while the production of agricultural and food products is widely represented in central Banat, west parts of Bačka and Srem.